The Survey of the Effect of Music on Performance of Physical Fitness Factors in Adolescent Boys - Farnaz Torabi; Kia Ranjbar; Zahra Soori (University of Tehran, 2013)
The aim of this study was to investigate the effect of external intervention factor (types of music) on physical fitness factors in adolescent boys. 30 adolescent boys (9-12 years old, MSD height, weight and BMI: 133.82.40 cm, 35.62.97 kg, and 19.91.21 kg/cm2), were selected and performed the tests in three stages (fast music, slow music, control) with Counter Balance method. In each stage, the muscular endurance, coordination, agility and muscular power tests were used. Also, fast rhythm (135-140 bpm) and slow rhythm (115-120 bpm) were used. Data were analyzed one-way analysis of variance (ANOVA) and Bonferroni post hoc test. The results showed that the changes in the results of muscular endurance tests including push up, sit-up and pull up were significant in all three stages (P<0.05).  The results of push up significantly outperformed those of control group in fast and slow music stages. There was a significant difference in sit-up and endurance strength between both intervention groups and control group (P<0.05). In each stage, the changes in the results of coordination tests were significant (P=0.01). The subjects outperformed in the control stage (no music) compared with the other stages (P<0.05). The agility results showed no significant difference among the three stages (P>0.05). The explosive power results showed significant differences in the fast music stage than control and slow music stages (P<0.05). Finally listening to the music during strength and endurance performances increases the efficiency of performance. Fast music maybe more effective in preventing central fatigue. On the other hand, every kind of music has negative effects on performance of coordination test and has no effect on performance of the agility test.